1999
DOI: 10.1086/ntj41789389
|View full text |Cite
|
Sign up to set email alerts
|

Is Charitable Giving by Nonitemizers Responsive to Tax Incentives? New Evidence

Abstract: Was nonitemizer giving responsive to the 1982-6 "above-the-line" tax deduction provided for in the 1981 Economic Recovery Tax Act? Here, a Tobit model is applied to Treasury Individual Tax Model file data for 1985 and 1986 to estimate the price elasticity of nonitemizer giving. Nonitemizer giving is found to be price-responsive. The responsiveness is, however, smaller than that for itemizer giving (at least for 1986 when the nonitemizer deduction was fully phased in), suggesting diminishing returns from extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The typical finding about the relationship of age with philanthropy in the literature is that it is positive (Alpizar, Carlsson, & Johansson-Stenman, 2008;Apinunmahakul & Devlin, 2004;Auten, Cilke, & Randolph, 1992;Auten & Rudney, 1990;Banks & Tanner, 1999;Bekkers, 2003Bekkers, , 2006bBekkers & Schuyt, 2008;Bekkers & Wiepking, 2006;Belfield & Beney, 2000;Boskin & Feldstein, 1977;Bristol, 1990;Brooks, 2002;E. Brown & Lankford, 1992;Bryant, et al, 2003;Carman, 2006;Carroll, et al, 2006;Chang, 2005;Choe & Jeong, 1993;Chua & Wong, 1999;Clotfelter, 1980;Duquette, 1999;Eaton, 2001;Eckel & Grossman, 2003;Eckel, et al, 2005;Eschholz & Van Slyke, 2002;Farmer & Fedor, 2001;Feenberg, 1987;Feldstein & Taylor, 1976;Frey & Meier, 2004aGreenwood, 1993;Hoge & Yang, 1994;Houston, 2006;Jones & Posnett, 1991a, 1991bKingma, 1989;Lankford & Wyckoff, 1991;List, 2004;Long, 2000;…”
Section: Agementioning
confidence: 99%
“…The typical finding about the relationship of age with philanthropy in the literature is that it is positive (Alpizar, Carlsson, & Johansson-Stenman, 2008;Apinunmahakul & Devlin, 2004;Auten, Cilke, & Randolph, 1992;Auten & Rudney, 1990;Banks & Tanner, 1999;Bekkers, 2003Bekkers, , 2006bBekkers & Schuyt, 2008;Bekkers & Wiepking, 2006;Belfield & Beney, 2000;Boskin & Feldstein, 1977;Bristol, 1990;Brooks, 2002;E. Brown & Lankford, 1992;Bryant, et al, 2003;Carman, 2006;Carroll, et al, 2006;Chang, 2005;Choe & Jeong, 1993;Chua & Wong, 1999;Clotfelter, 1980;Duquette, 1999;Eaton, 2001;Eckel & Grossman, 2003;Eckel, et al, 2005;Eschholz & Van Slyke, 2002;Farmer & Fedor, 2001;Feenberg, 1987;Feldstein & Taylor, 1976;Frey & Meier, 2004aGreenwood, 1993;Hoge & Yang, 1994;Houston, 2006;Jones & Posnett, 1991a, 1991bKingma, 1989;Lankford & Wyckoff, 1991;List, 2004;Long, 2000;…”
Section: Agementioning
confidence: 99%
“…But those religiously affiliated in Canada itemize rarely (Kitchen, 1992). Nonitemizers are less sensitive to changes in tax price (Duquette, 1999;Eaton, 2001). One reason may be that they don't know about the deduction (McGregor-Lowndes, Newton, & Marsden, 2006).…”
Section: Moderating Factorsmentioning
confidence: 99%
“…Married males are found to be more sensitive to the price of giving than married females (Andreoni & Payne, 2003). Price effects usually increase with income (G. E. Auten, Cilke, & Randolph, 1992;Duquette, 1999;Feldstein & Taylor, 1976;O'Neill, Steinberg, & Thompson, 1996;Robinson, 1990); some studies find that among the highest income groups price effects decline again (Boskin & Feldstein, 1977;Feldstein, 1975a;Taussig, 1967). A study of philanthropy in Singapore found that the tax price effect declined with education (Chua & Wong, 1999).…”
Section: Moderating Factorsmentioning
confidence: 99%
“…Actual disposable income Y. AGI alone cannot accurately forecast pretax income. To make the variable comparable to previous studies, pretax income equals AGI plus certain forms of income, including pension income, Social Security income, unemployment compensation, and individual retirement account (IRA) and Keogh plan distributions (Duquette 1999). This pretax income is then reduced by total federal income taxes, assuming there were no contributions to make disposable income exogenous to charitable giving.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%